Comprehensive microRNA and transcriptomic profiling of rheumatoid arthritis monocytes: role of microRNA-146b in pro-inflammatory progression. (2nd May 2021) - Ciechomska, Marzena; Wojtas, Bartosz; Bonek, Krzysztof; Roszkowski, Leszek; Gluszko, Piotr; Benes, Vladimir; Maslinski, Wlodzimierz
Abstract: Objective: To explore global miRNA and transcriptomic profiling of monocytes from RA patients compared with healthy controls in order to predict which aberrantly expressed miRNA can negatively modulate inflammatory molecules. Methods: Using next-generation sequencing, we have performed simultaneous global analysis of miRNA (miRNA-seq) and transcriptome (RNA-seq) of monocytes from RA patients and healthy controls. Global analysis of miRNA of SSc monocytes was also performed. Following differential analysis and negative correlation, miRNA–RNA pairs were selected. Results: We found that 20 specific miRNA candidates are predicted to silence inflammatory mediators, out of 191 significantly changed miRNAs in RA monocytes. Based on the highest scoring in terms of negative correlation ( r  = −0.97, P  = 1.75e–07, false discovery rate = 0.04) and the number of seeds in miRNA responsible for negative regulation, we selected miRNA-146b and its target gene anti-inflammatory retinoic acid receptor alpha ( RARA ). Similarly to next-generation sequencing, qPCR analysis also confirmed negative correlation between miRNA-146b and RARA expression ( r  = −0.45, P  = 0.04). Additionally, miRNA-146b expression in RA monocytes significantly correlated with clinical parameters including DAS28 for RA with CRP (DAS28-CRP) and ESR (DAS28-ESR), whereas overexpression of miRNA-146b was able to functionally reduce RARA expression in the human monocytic cell line THP-1. Finally, circulating miRNA-146b expression in sera and SFs was significantly elevated in RA patients. Conclusions: Overall, in this study we have identified a new miRNA-146b candidate that is predicted to negatively regulate the anti-inflammatory RARA transcript, whereas circulating miRNA-146b level can be used as a biomarker predicting pro-inflammatory RA progression and disease activity.